Exploring Attributes of Health Professions Educationists in their Workplace with the Lens of Bourdieu’s Theory of Practice: An Exploratory Study - Qureshi, Shaista Noor; Khaula Gul; Faiza Gulfam; Sulatana, Fouzia; Zainab Akbar; Sana Siddiqui (Pakistan Armed Forces Medical Journal, 2024)
Objective: To explore the attributes of health profession educationists in the departments of medical education in their institutions.Study Design: Exploratory qualitative study.Place and Duration of Study: Public and Private Sector Medical and Dental Colleges, Pakistan from Mar to Jul 2022.Methodology: The total number of participants was fifteen, including the Head of the Department and faculty members of DME. Consent was taken, and online scheduled interviews were conducted in English via Zoom software. The researcher recorded, transcribed, and analyzed the data manually. Another researcher rechecked it, and when saturation was achieved, data collection was stopped. The interviews were manually transcribed, followed by coding and thematic analysis of the data.Results: After thematic analysis, three Themes, 15 sub-themes, and 30 codes emerged. The themes were personality traits, working relationships, and commitment to excellence. For the successful accomplishment of DME's challenging tasks, HPE faculty are found to be altruistic, responsible, motivated, enthusiastic, resilient, work with passion, and humble. They are visionary, innovative, cooperative, and have multi-tasking and convincing capabilities. With these attributes, HPE faculty efficiently manage uncertainty and challenging situations.Conclusion: The Habitus (attributes of value-driven, resilience, hardworking, passionate, consistent, patient, visionary, and innovative) led to the execution of DME tasks despite limited field (resistance from administration, faculty, and organization) and capital (deficient human, infrastructural and financial resources)